(untitled) (LEARNing Landscapes, 2023)
In this article, we illustrate the experience of three literacy educators who harnessed online, collaborative platforms to cultivate community within their classrooms and with their colleagues. Through the use of creative practices including digital poetry, selfie collage, and curriculum sharing through video conferencing, the authors invited their students and professional peers to reflect on their perspectives and experiences related to social issues through the use of multimodal and media resources for composing. This article includes examples of creations from this context, including mentor text work, as well as implications for creativity and collaboration with students and colleagues.